Scientific Opinion on the energy conversion factor of d‐tagatose for labelling purposes - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal, 2016)
Abstract Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver a scientific opinion on the energy conversion factor of d‐tagatose to be used for calculating the energy value of foods to be declared in nutrition labelling. Energy conversion factors for nutrients for the purpose of nutrition labelling have been set based on the concept of metabolisable energy (ME). The same methodology has been applied to calculate the energy conversion factor for d‐tagatose in this opinion. The assessment is based on a dossier prepared for Nutrilab NV and submitted by Bioresco Ltd. At present, data are insufficient to derive an accurate ME value for d‐tagatose. Relying on the human data indicating a mean absorption rate of 80% (range 69–88%) and a urinary excretion of either 1% or 5%, the corresponding energy values for d‐tagatose would be 2.8 kcal/g (11.8 kJ/g) and 2.96 kcal/g (12.4 kJ/g), respectively. Taking into account that the remaining 20% of d‐tagatose which is not absorbed in the small intestine is fermented in the colon and may deliver at least some energy, e.g. in form of short‐chain fatty acids, the Panel concludes that a rounded estimate of the energy conversion factor for d‐tagatose based on the available data and calculated as ME would be 3 kcal/g (12.5 kJ/g). The Panel considers that additional data on the absorption, distribution, metabolism and excretion of d‐tagatose in humans would help in the calculation of a more accurate energy conversion factor for d‐tagatose based on the concept of ME.